Spatial Re-Utilization in Traditional Markets: Optimizing Trading Spaces for Pasar Jambe, Tangerang - Hanum, Nia Namirah; Tamami Madaniyah (Institut Teknologi dan Bisnis Ahmad Dahlan, 2025)
Traditional markets are often considered less optimal compared to modern markets, particularly in terms of comfort, circulation, and waste management. Although it was supposed to be operational since 2022, Pasar Jambe has yet to function and is crucial for meeting the basic needs of 52,521 residents of Jambe District in 2023. This study aims to design an alternative layout that not only fulfills the buying and selling functions but also enhances user comfort and supports trading activities and utilities such as ventilation, lighting, and waste management for sustainability and local economic growth. A descriptive method with a qualitative approach is used to identify the spatial needs of the market. The results indicate that the trading area should have a minimum area of 2 m² with a minimum circulation aisle of 1.5 m² and a radial design that facilitates access to each kiosk. The kiosks are designed with two opposing faces for efficiency and can be divided into two types to maximize display functionality. A waste container capacity of 2,000L is necessary to manage a total waste of 6,756 L/day, along with waste bins at each kiosk. This design also incorporates high ceilings and an optimal ventilation system to maintain the quality of fresh products, as well as optimized lighting through wide openings and a transparent twin wall Alderon roof, achieving 100 lux of illumination with a minimum ventilation of 20%.